The Etiology, Clinical Type, and Short Outcome of Seizures in Newborns Hospitalized in Besat Hospital/Hamadan/ Iran - SABZEHEI, Mohammad Kazem; BASIRI, Behnaz; BAZMAMOUN*, Hassan (Iranian Journal of Child Neurology, 2014)
How to Cite This Article: Sabzehei MK, Basiri B, Bazmamoun H. The Etiology, Clinical Type, and Short Outcome of Seizures in Newborns Hospitalized in Besat Hospital/ Hamadan/Iran. Iran J Child Neurol. 2014 Spring 8(2):24-28. Objective Seizures in neonates are very different from those of older children and adults. The aim of this study was to determine the etiology, clinical presentation, and outcome of seizures in hospitalized neonates of Besat Hospital, Hamadan, Iran. Material & Methods In this retrospective study, we evaluated all neonates with seizures (aged 0-28 days) admitted to the Besat hospital, Hamadan, over a period of three years from September 2008 to September 2011. The data were obtained from hospital records and analyzed using SPSS 12. Results Seizures were reported in 102/1112 (9.1%) neonatal admissions. Among neonates with seizures, 57% were male and 23.5% were preterm. The mean birth weight was 2936±677 grams and the mean gestational age was 37.60±1.94 weeks. 16.7% of them were LBW and 2.9% VLBW. In terms of seizure type, subtle seizures were observed in 38.2%, tonic in 29.4%, clonic in 26.4%, and myoclonic in 5.9% of cases. The main diagnosis in neonates with seizures included hypoxic-ischemic encephalopathy (HIE) (34.3%), infections (24.4%), intracranial hemorrhage (6.9%), hypoglycemia (5.9%), hypocalcemia (2.9%), inborn error of metabolism (1%), and unknown cause (24.5%). The mortality rate was 14.7%. Conclusion Neonatal seizures indicate a significant underlying disease. HIE was the most common cause of neonatal seizures in our study. Therefore, efforts should be made to improve care during childbirth. References 1. Mwaniki M, Mathenge A, Gwer S, Mturi N, Bauni E, Newton CR, et al. Neonatal seizures in a rural Kenyan District Hospital: aetiology, incidence and outcome of hospitalization BMC Medicine 2010;8:16. 2. Digra SK, Gupta A. Prevalence of seizures in hospitalized neonates. JK Science 2007;9(1):27-9. 3. Faiz N, Malik M, Azam M, Afzal U. Etiology and type of neonatal seizures, Ann Pak Inst Med Sci 2009;5(2):77-86. 4. Aftab R. Neonatal seizures: Etiology, Clinical types and outcome. Professional Med J 2007;14(2):199-203. 5. Fakhraee SH. Neonatal seizures: A Review. Iran J child Neurol 2007:1(4):7-11. 6. Sheth RD, Hobbs GR, Mullett M. Neonatal seizure: Incidence, onset and etiology by gestational age. J Perinatol 1999;19(1):40-3. 7. Saliba RM, Annegera Jf, waller DK, Tyson JE. Incidence of Neonatal seizures in harris county, American Journal of epidemiology 2000,150(7):763-9. 8. Moayedi AR, Zakeri S, Moayedi F. Neonatal seizures: Etiology and type. Iran J child Neurol 2007:23-6. 9. Ronen GM, Penney S, Andrew W. The epidemiology of clinical neonatal seizure in new found land, a populationbased study. J Pediatr 1999;134(1):71-5. 10. Arpino C, Domizio S, Carrieri MP, Brescianini DS, Sabatino MH, Curatolo P. Prenatal and perinatal determinants of neonatal seizures occurring in first week of life. Abs J child Neurol 2001:16(9):651-6. 11. Tekgul H, Gauvrea K, Soul J, Murphy L, Robertson R, stewart J, et al. The current etiology profile and neurodevelopmental outcome of seizures in term newborn infants. Pediatrics 2006;117(4):1270-80. 12. Udani V. Long-term prognosis of neonatal seizure – where are we? Indian pediatr 2008;45(9):739-41. 13. Ross AL, Lombroso CT.Neonatal seizures state. A study of clinical, pathological, and electroencephalographic features in 137 full-term babies with a long-term followup. Pediatrics 1970;45(3):404-25. 14. Taksande A, Vilhecar K, Jain M, Lakra M. Clinico-Biochemical Profile of Neonatal Seizures. Indian J Pediatr 1995;52:424-7. 15. Legido A, Clancy RR, Berman PH. Neurologic outcome after electroencephalographically proven neonatal seizures. Pediatrics 1991;88(3):583-96. 16. Malik BA, Butt MA, Shamoon M, Tehseen Z, Fatima A, Hashmat N. Seizures etiology in the newborn period. J Coll Physicians Surg Pak 2005;15(12):786-90. 17. Nunes ML, Martins MP, BareaBM, Wainberg R C, Costa da Costa J. Neurological outcome of newborns with neonatal seizures. Arq Neuropsiquiatr 2008;66(2A):168-74. 18. Taghdiri MM, Emadi M, Tavasoli AR. Plain CT Scan in neonatal convulsion. Iranian Red Crescent Medical Journal 2005;7(3):43-45. 19. Taghdiri MM, Eghbalian F, et al. Auditory Evaluation of high risk newborn by automated auditory brain stem response. Iranian J Pediatric 2008 Dec; 18(4):330-334.